Strategies to Prevent Illegal Importation of Dangerous Goods as an Effort to Build National Resilience - Wanto, Alfi Haris; Efendi, Yusuf; Domai, Tjahjanulin (Faculty of Law, Universitas Pekalongan, 2024)
The Unitary State of the Republic of Indonesia (NKRI) is a country that is mostly archipelago. The era of globalization makes the state continue to evaluate its defense capabilities in the face of threats whose forms and patterns have changed, including the entry of dangerous goods. Customs and Excise is one of the law enforcers at sea, primarily related to supervising customs and excise activities. The purpose of writing this paper is to prevent strategies to prevent the illegal importation of dangerous goods in building national resilience by the role of customs and excise as a community protector by using 4 (four) strategy implementation factors, namely management, organizational structure, organizational culture, and organizational information systems. The author uses qualitative research methods with data collection techniques, such as interviews, observation, and documentation. From the research conducted, it can be concluded that the placement of employees has not included particular expertise, the existence of joint programs to maximize supervisory activities, the use of machines in supervisory activities, the leadership has encouraged organizational culture, the organizational structure is by the regulations, the creation of the AN.TA.RE.J.A application (analyzing, targeting and reporting for joint programs) in supporting supervisory activities.